Biological characterization of a biodegradable scaffold for common bile duct replacement in an experimental model - Barrera-Mera, Baltazar; Barrera-Miranda, Ely de los Angeles; Sarmiento-González, María José; Abundez-Pliego, Ana Lilia; Olivares-Cruz, Sandra; Valderrama-Treviño, Alan I. (International Journal of Research in Medical Sciences, 2023)
Background: The nanofiber scaffolds achieved by the electrospinning technique have been used to develop several biological tissues, the nanofibers obtained by electrospinning procure a favorable microenvironment to mimic the extracellular matrix. Methods: Study type was of experimental. Study conducted at National Autonomous University of Mexico, from May 2018- May 2022. The protocol was approved by the research and ethics commissions of the UNAM school of medicine. A viscoelastic solution of polylactic-co-glycolic acid (PLGA) and polycaprolactone (PCL) in a 70:30 ratio and gelatin (Gel) in an 80:20 ratio was prepared while a dynamic collector was used with the electrospinning technique. Results: Mechanical and biological tests were carried out on the scaffold obtained by electrospinning; the resultant scaffold achieves good mechanical matching and structural similarity between the graft and the extrahepatic bile duct. Conclusions: In this study we managed to create a porous, biocompatible scaffold with good cell adhesion and proliferation, potentially applicable to tissue engineering, especially for the replacement of tubular organs such as blood vessels, bile ducts, and urethra.